THE ROLE OF PEDAGOGICAL COACHING IN PREVENTING BULLYING AMONG STUDENTS (Psychology Travelogs, 2025)
The article examines the role of pedagogical coaching in creating a safe educational environment and preventing bullying among students. The purpose of the study is to analyze the impact of pedagogical coaching on the development of emotional competence, reducing conflict and creating positive interaction in student groups. It was determined that pedagogical coaching is an effective tool for supporting students in the process of developing self-regulation, empathy and communication skills, which are extremely important in preventing bullying.The practical part of the study was conducted among 60 students of Lyceum No. 2 of the Khmelnitsky City Council of middle school age. 30 respondents of the experimental group participated in a coaching program aimed at increasing emotional competence. The program included a number of trainings, individual consultations and group trainings. The main focus was on developing the skills of identifying and managing one's own emotions, improving students' ability to constructively resolve conflicts, and creating an atmosphere of mutual respect in teams. Practical classes were also held to reduce manifestations of aggressive behavior, develop tolerance, and social cohesion.The results of the study showed positive changes among the program participants: the level of aggressiveness significantly decreased, the number of situations of constructive conflict resolution increased, students demonstrated a higher level of empathy and readiness for interaction, and also noted a decrease in manifestations of bullying, increased mutual trust, and improved emotional climate in classes. At the same time, the changes recorded in the control group are not statistically significant and do not indicate a reliable improvement in emotional competence indicators or a decrease in the level of conflict.Based on the results obtained, a conclusion was drawn about the high effectiveness of pedagogical coaching as a tool for preventing bullying among students. The use of a coaching approach contributes not only to the improvement of emotional competence, but also to the creation of conditions for the formation of a safe educational environment, which is an important aspect of modern pedagogical practice. The results obtained can be used to develop bullying prevention programs in educational institutions.
Keywords: aggression; safe educational environment; bullying; emotional competence; conflict; pedagogical coaching; student team